Effectiveness of neem based biopesticide to enhance rice (Oryza sativa) productivity - Kamarulzaman, P.S.D. (Elsevier B.V., 2018)
Rice contributes towards food security and consumed widely by about 2 billion people in Asia. Losses because of pest and diseases are considered as the main constraints in rice production. Wide ranges of methods have been applied to control pests however conventional pesticide is the most widely practice. Biopesticide which is more environmental friendly can be the alternative for paddy cultivations. Bioactive secondary metabolite azadirachtin compound which is present in neem (Azadirachta indica) could be used to produce effective biopesticide that possesses insecticidal properties. The effectiveness of the biopesticide derived from neem is assessed with its application on the actual paddy field and compared with conventional pesticide with niclosamide as its active ingredient. The paddy yield component and paddy yield were recorded and the traits associations are determined using statistical analysis. Descriptive data of biopesticide for range, mean and standard deviation of yield components such as number of panicle per m2 (368.8 ± 11.4), panicle length (25.3 ± 0.19), percentage of productive spikelets per panicle (80.8 ± 1.13), 1000 grains weight (27.7 ± 0.10) and grains yield per m2 (1151.3 ± 46.8) were notably higher than conventional pesticide. Biopesticide showed higher rice yield components at 5 level of significance as indicated by t-test analysis. Based on the results, the productivity of rice yield after application of biopesticide was verified to be positive interdependent with the components studied. Higher grain yield is obtained for biopesticide with higher positive association among the grain yield and yield components which offered an alternative for healthier rice cultivation. © 2017 Elsevier B.V.